Pancasila as Strategy to Prevent Proxy War - Siswanto Siswanto (The Republic of Indonesia Defense University, 2017)
This article aim to contribute an idea regarding the importance of returning Pancasila as the state ideology and way of life to prevent Indonesia from going into deeper trap of nation problems. Pancasila as the ideology and life perspective has been abandoned by most of Indonesian citizens. It is not surprising that the Indonesian people are exposed to several national issues, such as horizontal conflicts, moral crises, economic disparities, and the threat of disintegration. All of this problem has a potential to trigger proxy war. This article is using three dimension framework of ideology, including, reality, ideal, and flexibility dimension. This study conclude that actualizing Pancasila may address the nation issues in Indonesia.